(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The static response of two-dimensional horizontal layered piezoelectric bounded domain with side face load was investigated. In this paper, the modified scaled boundary finite element method (SBFEM) is provided as an effective semi-analytical methodology. The method is used to solve the static problem for the layered piezoelectric bounded domain. The scaling line definition extends the SBFEM to be more suitable for analyzing the multilayered piezoelectric bounded domain. It avoids the limitations of original SBFEM in modeling the horizontal layered bounded domain. The modified SBFEM governing equation with piezoelectric medium is derived by introducing Duality variable in the Hamilton system. This derivation technology makes the progress concise. The novel displacement and electric governing equations of the modified SBFEM are given together for the first time. The node forces can be expressed as power exponent function with radial coordinate by introducing the auxiliary variable and using the eigenvalue decomposition. The novel modified SBFEM solution of layered bounded domain with piezoelectric medium is solved. The new power expansion function of layered piezoelectric medium with side face load is proposed. This technology significantly extends the application range of modified SBFEM. The novel treatment of side face load for the layered piezoelectric bounded domain is proposed. Numerical studies are conducted to demonstrate the accuracy of proposed technique in handling with the static problem of layered bounded domain with piezoelectric medium for side face load. The influence of the side face load type and depth is discussed in detail.